2000
DOI: 10.1073/pnas.190274097
|View full text |Cite
|
Sign up to set email alerts
|

A biosensor assay for studying ligand-membrane receptor interactions: Binding of antibodies and HIV-1 Env to chemokine receptors

Abstract: The HIV envelope (Env) protein mediates entry into cells by binding CD4 and an appropriate coreceptor, which triggers structural changes in Env that lead to fusion between the viral and cellular membranes. The major HIV-1 coreceptors are the seven transmembrane domain chemokine receptors CCR5 and CXCR4. The type of coreceptor used by a virus strain is an important determinant of viral tropism and pathogenesis, and virus-receptor interactions can be therapeutic targets. However, Envs from many virus strains int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 38 publications
3
94
0
Order By: Relevance
“…Consistent with other groups, we observed that gp120 used at 80 nM rarely induced detectable phosphorylation of Erk-1/2, while it did cause chemotaxis. In contrast, gp120 tested at 200 nM, a concentration close to its K d for CXCR4 (47,48), did cause Erk-1/2 phosphorylation in unstimulated CD4 ϩ T cells from most donors. This threshold effect suggests that triggering the MAPK pathway requires a higher occupancy of receptors as compared with other pathways.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Consistent with other groups, we observed that gp120 used at 80 nM rarely induced detectable phosphorylation of Erk-1/2, while it did cause chemotaxis. In contrast, gp120 tested at 200 nM, a concentration close to its K d for CXCR4 (47,48), did cause Erk-1/2 phosphorylation in unstimulated CD4 ϩ T cells from most donors. This threshold effect suggests that triggering the MAPK pathway requires a higher occupancy of receptors as compared with other pathways.…”
Section: Discussionmentioning
confidence: 75%
“…1A). Experiments with gp120 were conducted at 200 nM, a concentration close to its reported K d for CXCR4 (200 -500 nM) (47,48), to achieve significant occupancy of the receptor. PBMC membranes pulsed with gp120 showed an increase in [ 35 S]GTP␥S binding, though the response was lower than that induced by SDF-1.…”
Section: Gp120 Activates Heterotrimeric G Proteins and Induces Calciumentioning
confidence: 99%
“…1G) concurs with observations of activated p38 in lymph node biopsies from untreated HIV-1 patients (52). However, other reports in primary CD4 T cells suggest that gp120 ligation to CXCR4 can activate Akt, ERK, and Ca 2ϩ mobilization (53,54); however, those studies used gp120 X4 at concentrations of 10 -20 nM to induce calcium mobilization and modest Akt activation (54), or very high concentrations of gp120 ϫ4 (200 nM), which is close to its K D for CXCR4 (55) to induce activation of Akt and ERK (53). We observed only very weak Akt and ERK activation at 85 nM gp120IIIB (data not shown), yet gp120 at 4.2 nM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…gp120 proteins tend to bind to CCR5 with affinities between 4 and 15 nM (21,56). For CXCR4, laboratory-adapted HIV-1 strains and primary R5X4 isolates bind more weakly, with K d s of between 200 and 500 nM (3,28). Whether relatively poor affinity for CXCR4 will prove to be a general feature of X4 HIV-1 strains is not known, though high-affinity interactions with CXCR4 are possible, as evidenced by HIV-2 VCP and HIV-2 ROD/B (35 CXCR4-positive cells independently of CD4 (24,43), due perhaps in part to their high affinity for this coreceptor.…”
Section: Discussionmentioning
confidence: 99%